Eksekusi Putusan Pengadilan yang Berkekuatan Hukum Tetap oleh Juru Sita Pengadilan Negeri Bengkalis: Studi Putusan Nomor 3/Pdt/G/2023/PN.Bls - Pangoloi Tampu Bolon; Ahmad Ansyari Siregar; Nimrot Siahaan (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study examines the execution of a court judgment that has obtained final and binding legal force (inkracht) by the Bailiff of the Bengkalis District Court in an inheritance dispute case Number 3/Pdt/G/2023/PN.Bls. Using a sociological legal research method, data were collected through interviews and field observations and analyzed using a qualitative descriptive approach. The findings indicate that the execution of the inherited property has not been successfully carried out. The main obstacles include physical resistance from the losing party supported by a community organization, as well as financial constraints faced by the applicant in covering the costs of coordinating security measures with the police. These findings demonstrate that the executorial power of court judgments is still strongly influenced by social factors and the court’s managerial readiness in conflict mitigation.